2010
DOI: 10.1128/jvi.02264-09
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear RNA Export and Packaging Functions of HIV-1 Rev Revisited

Abstract: Although the viral Rev protein is necessary for HIV replication, its main function in the viral replication cycle has been controversial. Reinvestigating the effect of Rev on the HIV-1 RNA distribution in various cell lines and primary cells revealed that Rev enhanced cytoplasmic levels of the unspliced HIV-1 RNA, mostly 3-to 12-fold, while encapsidation of the RNA and viral infectivity could be stimulated >1,000-fold. Although this clearly questions the general notion that the nuclear export of viral RNAs is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 50 publications
(43 reference statements)
5
86
0
Order By: Relevance
“…In Hgp syn ⌬MA, the MA domain of Hgp syn was replaced with the myristoylation signal of the protooncogene c-src (nt 450 to 491 of GenBank entry NM_005417.3). Proviral and vector constructs HXB2⌬env⌬nefCAT (formerly pHXB⌬envCAT [64]), NL4.3Re (formerly HIV RevϪ [6]), and V H (7) were described previously. Plasmids NL4.3Reg**, NL4.3Re-mutCA, and NL4.3Re⌬MA are derivatives of NL4.3Re.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hgp syn ⌬MA, the MA domain of Hgp syn was replaced with the myristoylation signal of the protooncogene c-src (nt 450 to 491 of GenBank entry NM_005417.3). Proviral and vector constructs HXB2⌬env⌬nefCAT (formerly pHXB⌬envCAT [64]), NL4.3Re (formerly HIV RevϪ [6]), and V H (7) were described previously. Plasmids NL4.3Reg**, NL4.3Re-mutCA, and NL4.3Re⌬MA are derivatives of NL4.3Re.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear and cytoplasmic fractions were isolated essentially as described previously (6,7,36). Two days after transfection, HEK 293T cells were detached and washed in cold PBS (Invitrogen).…”
Section: Figmentioning
confidence: 99%
“…Consistent with an enhanced polysomal association of the RRE-containing RNAs, Rev was also found to stimulate protein expression levels to a greater extent than the cytoplasmic mRNA levels, suggesting an independent stimulatory effect of Rev on translation (recently reviewed by Groom et al, 2009). More recently, we also observed that Rev enhances encapsidation of the genomic RNA into virions to a much larger extent than it affects cytoplasmic RNA levels (Blissenbach et al, 2010;Brandt et al, 2007). Nuclear RNA export, the corresponding modulation of the ratio of differentially spliced transcripts in nucleus and cytoplasm, the increase in translational efficiency, and stimulation of encapsidation are all exerted during the late phase of the virus replication cycle and, until now, no Rev mutants have been reported to be differentially impaired for one or several of these functions.…”
Section: Known Functions Of Rev In the Late Phase Of The Replication mentioning
confidence: 80%
“…36,37 Additionally, evidence suggests that the presence of Rev than 1,000 fold. [60][61][62][63] Interestingly, this latter activity of Rev was in part linked to the nuclear export of RNA suggesting that this apparent activity of Rev may lie in its ability to modulate nuclear RNP (ribonuclear protein) assembly on RRE containing RNAs. [60][61][62] It was observed that in cells expressing similar amounts of different forms of HIV-1 RNA, Rev/ RRE dependent viral RNA encapsidation was 100 fold higher than similar viral Figure 1.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…[60][61][62] It remains to be determined if a TMG-PIMT/Rev interaction may also influence the encapsidation of viral genomic RNA. Preliminary analyses of HIV-1 virion RNAs suggest the presence of TMG-capped moieties (Yedavalli VS, unpublished results).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%